Pengimplementasian Hak Sosial Antara Pejabat dan Masyarakat di Negara Indonesia - Edy Soesanto; Shiva Nabila; Muhammad Areevo Al Islami Putra (International Forum of Researchers and Lecturers, 2025)
This paper analyzes the implementation of citizenship rights in Indonesia, focusing on the interaction between public officials and the public. The important role of officials in policy making and implementation, as well as the active role of the public in participation and oversight, are discussed in depth. In addition, the article also presents some solutions to overcome these problems, with the aim of improving the quality of citizens' rights implementation. The implementation of citizenship rights between officials and the public in Indonesia is a complex and dynamic process. Despite the challenges, a commitment to democratic principles and the protection of citizens' rights can strengthen the relationship between officials and communities. With an inclusive and participatory approach, Indonesia can build a more just, transparent and sustainable society. The value of equality means that every citizen has equal rights, equal obligations, and equal standing before the law and government. This value in this reform era is very decisive for the journey of life in society, nation and state, as a signpost in achieving national ideals and national goals. Public participation in the political and decision-making process is essential to maintain the sustainability of democracy. People have the right to be involved in the discussion and determination of policies that affect their lives. Through elections, public forums and various other participatory mechanisms, people can express their aspirations and control public officials. This study analyzes the level of political participation in general elections in rural Indonesia. Through a survey of a number of respondents, this research identifies factors that influence political participation, such as education level, political awareness, and access to information. The results show that the level of political participation in rural areas is still low and is influenced by several obstacles. This research suggests the importance of improving the quality of political education and providing adequate infrastructure to increase people's political participation. As the subject of citizens' rights, the community has a very important role in ensuring these rights are realized. This paper discusses how the community can play an active role in political participation, oversight of the government, and in demanding their rights. The challenges faced by the community in carrying out this role, as well as efforts to increase community participation, are also reviewed.